Active Modulating the Intensity of Bifocal Metalens with Electrically Tunable Barium Titanate (BTO) Nanofins - Shuai Qin; Hui Huang; Kaiqian Jie; Sirui Zeng; Li Chen; Hongzhan Liu; Jianping Guo; Hongyun Meng; Faqiang Wang; Xiangbo Yang; Zhongchao Wei (Nanomaterials, 2021)
The multifocal metalens with an adjustable intensity has great potential in many applications such as the multi-imaging system, but it is less studied. In this paper, by combining the electro-optic material barium titanate (BTO) with the Pancharatnam-Berry phase, an electrically modulated bifocal metalens in a visible light band is innovatively proposed. Due to the electro-optic effect, we can control the refractive index of the BTO nanofins to vary between 2.4 and 3.07 by applying different voltages (0–60 V). Thus, the method of modulating the intensity ratio of the two focal points is applying an electric field. It is different from using phase change materials or changing the ellipticity of incident light, the strategies proposed in previous studies. Moreover, when the applied voltage is 0 V or 60 V, the bifocal metalens becomes a single focal metalens with different focal lengths, and the full width at half maximum of each focal point is close to the diffraction limit. It has great potential in applications of optical storage, communication and imaging systems.